TURNOVER INTENTION DITINJAU DARI WORKPLACE BULLYING, WORKPLACE SPIRITUALITY, DAN SELF-ESTEEM - Fitriyani, Nur Farah; Luzvinda, Liany (TAZKIYA JOURNAL OF PSYCHOLOGY, 2019)
AbstractThe purpose of this study is to find out what variables affect employees who tend to turn out or stay in the company. In this study predicted workplace bullying, workplace spirituality and self esteem, affect employee turnover. Subjects in the study were 206 stewardesses who were obtained by accidental sampling technique. Test the validity of measuring instruments using confirmatory factor analysis (CFA) techniques. Data analysis uses multiple regression analysis techniques. The results showed that there was a significant effect of workplace bullying, workplace spirituality and self-esteem on turnover intention. Minor hypothesis test results show that inner life and meaning and purpose in work significantly affect turnover intention. In contrast, work-related bullying, person-related bullying, physical bullying, and self-esteem are not significant in influencing turnover intentionAbstrakTujuan penelitian ini adalah untuk mengetahui variabel apa saja yang mempengaruhi  karyawan cenderung memilih  keluar (turnover) atau bertahan dalam perusahaan. Dalam penelitian ini diprediksi workplace bullying, spiritualitas ditempat kerja dan  self-esteem, berpengaruh terhadap turnover karyawan. Subyek pada penelitian berjumlah 206 Pramugari yang diperoleh dengan tehnik accidental sampling. Uji validitas alat ukur menggunakan teknik confirmatory factor analysis (CFA). Analisis data menggunakan teknik analisis regresi berganda. Hasil penelitian menunjukan bahwa ada pengaruh yang signifikan workplace bullying, workplace spirituality dan self-esteem terhadap turnover intention. Hasil uji hipotesis minor menunjukkan bahwa inner life dan meaning and purpose in work secara signifikan mempengaruhi turnover intention. Sebaliknya, work-related bullying, person-related bullying, physical bullying, dan self-esteem tidak signifikan dalam mempengaruhi turnover intention